Integrated Rice Fish Farming System in Arunachal Pradesh: An Over View - Hussain, S. M.; Debnath, P.; Sen, D.; Pathak, M.; Nabam, J.; Baruah, D. (Indian Journal of Hill Farming, 2018)
Rice-fish culture (RFC) is a type of farming system in which rice is the main enterprise and fish are taken as additional means for nutritional security and extra income. This system may open a new horizon to improve farmer’s socio-economic conditions enhancingland use efficiency at low inputs and by waste recycling. Integrated Rice Fish Farming System under either capture systems or culture systems is a low-cost sustainable practice to obtain high value protein food and minerals. A total of 04 villages of East Siang district and 04 village of Ziro area of Lower Subansiri district of Arunachal Pradesh were surveyed during Kharif and Rabi seasons of 2015 and 2016 cropping season to evaluatethe economic viability and acceptability of Integrated Rice Fish Farming System. Evaluating the multilocational report on Integrated Rice Fish Farming System it has been observed that 90% of the farmers release fish seed in the ranged from 3.0 cm to 5.0 cm size in their rice field during the month of April and July in Lower Subanshiri and East Siang districts, respectively . It was also found that survival rate of advanced fry was between 42 % and 47 % with an average weight of 0.075 kg to 0.110 kg at harvesting for both of the districts. The average net income in RFC was Rs. 45,876 and Rs. 43,713 in Lower Subansiri and East Siang district respectively, while in sole cropping of rice it was Rs. 29,694 and Rs. 32,904, respectively. The additional income of Rs. 16,182 and Rs.10,809 were gained by adopting the RFC system as compared to sole cropping of rice.